Boundary between hadron and quark-gluon structure of nuclei - Pirner, Hans J.; Vary, James P. (Physical review. C, Nuclear physics, 2011)
We show that the boundary between quark-dominated and hadron-dominated regions of nuclear structure may be blurred by multinucleon quark clusters arising from color percolation. Recent experiments supporting partial percolation in cold nuclei and full percolation in hot/dense nuclear matter include deep inelastic lepton-nucleus scattering, relativistic heavy-ion collisions, and the binding energy in 5HeΛ.
Gesehen am 15.12.2022